2019
DOI: 10.4149/gpb_2019034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicorandil on vascular and renal dysfunctions in adenine-induced nephropathy: Possible underlying mechanisms

Abstract: Vascular dysfunctions in chronic kidney disease (CKD) include endothelial dysfunctions and vascular calcification (VC). In the present study, we examined the possible protective effect of nicorandil (potassium channel opener) on renal and vascular dysfunctions in a rat model of adenine-induced nephropathy and its underlying mechanisms. Thirty-four male Sprague-Dawley rats were randomly allocated into 3 groups: Control group, Adenine group (animals received high-adenine diet for 4 weeks), and Nicorandil group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…[12][13][14][15][16][17][18][19] There are numerous animal models that have been used to elucidate the pathological mechanisms of kidney disease. [19][20][21] Those induced by ischemia, 14,22,23 lipopolysaccharide, [24][25][26][27] cisplatin, [28][29][30] arsenic, [31][32][33] adenine, [34][35][36] cadmium 15,[37][38][39][40] and diabetes [41][42][43][44][45][46] are widely used as animal models of kidney disease. These models have also been used to test the therapeutic effect of a given drug or compound.…”
mentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19] There are numerous animal models that have been used to elucidate the pathological mechanisms of kidney disease. [19][20][21] Those induced by ischemia, 14,22,23 lipopolysaccharide, [24][25][26][27] cisplatin, [28][29][30] arsenic, [31][32][33] adenine, [34][35][36] cadmium 15,[37][38][39][40] and diabetes [41][42][43][44][45][46] are widely used as animal models of kidney disease. These models have also been used to test the therapeutic effect of a given drug or compound.…”
mentioning
confidence: 99%
“…16,23 Clinical practices have indicated that nicorandil can dilate coronary vessels, increase coronary blood flow, and relieve coronary vasospasm without affecting heart rate, myocardial contractility, myocardial oxygen consumption, or atrioventricular conduction time. [16][17][18][19][20][21][22] Nicorandil is recommended for all types of angina pectoris, especially for spastic angina pectoris. Studies have also confirmed that nicorandil can significantly reduce the incidence of cardiovascular events associated with CHD and improve the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to improving heart function, nicorandil was reported to provide additional renal protection for CKD and reduce the incidence of contrast-induced nephropathy in patients undergoing coronary angiography or interventional therapy. 10,17 Therefore, we investigated the effect of nicorandil on renal function and renal injury in patients with type 1 CRS. We found that both conventional standard treatment and additional nicorandil treatment could improve traditional renal function indexes (Scr and Cys-C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reports that pretreatment with nicorandil (K ATP channel opener) causes upregulation of Nrf2 mRNA in the aortic tissues of rats fed with an adenine-rich diet, suggesting that the improvement of oxidative stress in the aortic tissue could reduce the CDK-associated aortic calcifications [5].…”
mentioning
confidence: 99%